Doctor-patient relationships (DPR) in China: managers and clinicians’ twofold pathways from commitment HR practices - Ma, S.; Xu, X.; Trigo, V.; Ramalho, N. J. C. (Journal of Health Organization and Management, 2017)
Purpose: The first objective of this research is to develop and test theory on how commitment human resource (HR) practices affect hospital professionals’ job satisfaction that motivates them to generate desirable patient care and subsequently improve doctor-patient relationships (DPR). The second objective is to examine how commitment HR practices influence in different ways hospital managers and clinicians. Methodology: Using a cross-sectional survey, data were collect from 508 clinicians and hospital managers from 33 tertiary public hospitals in China. Structural Equation Model (SEM) was employed to test the relationships among the constructs. Results: Commitment HR practices positively affect the job satisfaction of the healthcare professionals surveyed. Results also show that they perceive a positive relationship between job satisfaction and DPR. Overall, the model indicates a reversal on the strongest path linking job satisfaction and DPR whereby managers’ main association operates through extrinsic job satisfaction while for clinicians it occurs through intrinsic job satisfaction only. Implications for Practice: DPR may be improved by applying commitment HR practices to increase both healthcare professional’s intrinsic and extrinsic satisfaction. In addition, intrinsic factors may serve as stronger motivators for clinicians rather than hard economic incentives in achieving DPR improvements. Originality/value: This study contributes to the small but growing body of research on HRM in the healthcare sector with new evidence from the perspective of clinicians and hospital managers in the Chinese hospital context. It also demonstrates the importance of effective HRM in improving both hospital managers and clinicians’ work attitudes.